THE INFLUENCE OF THE ILMAN WA RUUHAN METHOD IN INCREASING THE SPEED ​​AND ACCURACY OF STUDENTS' MEMORIZING THE QUR'AN - Febriandi, Erfan; Riyadi, Slamet; Sriwardona (Mandeh : Jurnal Pendidikan Islam, 2025)
The background of this research is that students face various challenges in memorizing the Qur'an, even though they have a great interest and have memorized a lot. The main problem is the slow memorization process and memorization that is easily lost. The causal factors are various, both from within the student (such as time management) and external (family and school environment). This study aims to test the effect of the Ilman Wa Ruuhan Method on the speed and accuracy of students' memorization of the Qur'an. This study uses a quantitative method with a correlational and Ex-post facto approach, this study involved all students as samples. Data were obtained through a Qur'an memorization test and a questionnaire about the Ilman Wa Ruuhan method. The results of the analysis showed a significant positive correlation (r = 0.693), proving that the Ilman Wa Ruuhan method has an influence of 48.025% on the speed and accuracy of students' memorization of the Qur'an. The remaining 51.975% is influenced by other factors. The t-test also supports this finding, with a p-value smaller than α(0.05) confirming the significant influence of the Ilman Wa Ruuhan method on students' Quran memorization speed and accuracy. The implications of this research can serve as baseline data for future researchers in examining this issue in different contexts and issues.